Drill Hole Sets Manufacturing on CNC Machines. (2015) - Ioan, Mocian; Razvan, Cazacu
Abstract: This research proposes an optimized methodology to generating the programs needed for the manufacturing of parts with numerous drill holes on drilling and milling machines. The authors present this new approach and an application that implements it. The application and its accessible user interface is powerful and easy to use by the CNC programmers. The data is modeled in a structure that makes it natural for the engineer to handle while allowing the construction of automation algorithms at the same time. Initial data can be supplied directly inside the application GUI or imported from an exterior spreadsheet file produced by applications such as Excel or generated using code by other applications such as AutoCAD. The application can be extended with any number of postprocessors in order to output specific program syntax for any machine while keeping the core preprocessor and processor intact.